ANALYSIS OF FACTORS WHICH CAUSED STATEMENT OF BUDGETING OF APBN FUNDS IN THE END OF THE BUDGET YEAR IN THE WORKING UNITS OF SCOPE OF PAYMENT OFFICE OF BLITAR COUNTRY SERVICES - Evita Intan Saputri (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2020)
APBN which tends to increase every year, but not followed by a good absorption pattern. This causes a buildup of disbursement of APBN funds at the end of the fiscal year. This can result in losses for the country. This study discusses the factors that caused the accumulation of disbursement of APBN funds at the end of the fiscal year. This study aims to analyze the factors that cause the accumulation of disbursement of APBN funds at the end of the fiscal year in the scope of payment of the Blitar State Treasury Service Office. The method used is a quantitative associative type. Direct researchers give questionnaires to respondents to get data. The results of data analysis showed that the eight factors consisted of administration, human resources, planning, procurement of goods and services, mutations of officials, providers of goods and services, regulations, and internal. Factors of official and internal mutations affect the buildup of funds disbursement. While administrative factors, human resources, planning, procurement of goods and services, providers of goods and services, and regulations have no effect. In silmutan administration, human resources, planning, procurement of goods and services, mutations of officials, providers of goods and services, regulations, and internal positive and significant effect on the accumulation of disbursement of APBN funds.